Earnings Persistence Determinants in Indonesia’s Automotive Industries - Latifah, Yuni; Hernawati, Erna (EQUITY, 2024)
The financial performance of companies, particularly as reflected in financial statements, is crucial for decision-making. Earnings persistence, which is defined as the ability of a company to maintain stable earnings from one period to the next, is a key indicator in assessing the financial health and stability of a company. This research aims to analyze the patterns, trends, and best strategies in the use of digital technology and digital transformation implemented by companies in the global market.  The study's population includes automotive sub-sector companies, and their components listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023, with purposive sampling serving as the sampling method, and 18 companies were selected as the samples. The technique applied for data analysis is the multiple regression method. The discoveries from this research prove that company size, accrual reliability, and book tax differences do not significantly affect earnings consistency. Meanwhile, the debt ratio has a significant effect on earnings persistence. Keywords: Firm Size; Accrual Reliability; Book Tax Differences; Debt Asset to Ratio; Earning Persistence.